UPAYA PERLINDUNGAN HAK CIPTA KONTEN YOUTUBE WNA YANG DIJIPLAK OLEH WNI DALAM PERSPEKTIF BERN CONVENTION - Ayu Indirakirana; Ni Ketut Millenia Krisnayanie (Ganesha Law Review, 2021)
Intellectual Property Rights are rights relating to property arising from human intellectual abilities. This ability can be in the form of works in the fields of technology, science, art and literature. The development of technology today is very supportive of the development of a person's creative work which is increasingly diverse with high creativity. One of the media that is currently widely used is youtube. Video uploaded on social media youtube is one of the copyrighted works protected by copyright by law, namely Law Number 28 of 2014 concerning Copyright. However, in practice there are still frequent violations of video copyright works which are the property of an author. One of the violations that often occurs is the plagiarism of foreign YouTube content by Indonesian citizens. Plagiarism of other people's work of YouTube content is a copyright infringement. Copyright is an important topic for the YouTube community. Intellectual Property Rights are so important in relations between nations, they are closely related to international trade.